Transcranial direct current stimulation (tDCS) over the left prefrontal cortex does not affect time-trial self-paced cycling performance: Evidence from oscillatory brain activity and power output - Holgado, D.; Zandonai, T.; Ciria, L. F.; Zabala, M.; Hopker, J.; Sanabria, D. (PLOS ONE, 2018)
Objectives: To test the hypothesis that transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex (DLPFC) influences performance in a 20-min time-trial self-paced exercise and electroencephalographic (EEG) oscillatory brain activity in a group of trained male cyclists. Design: The study consisted of a pre-registered (https://osf.io/rf95j/), randomised, sham-controlled, single-blind, within-subject design experiment. Methods: 36 trained male cyclists, age 27 (6.8) years, weight 70.1 (9.5) Kg; VO2max: 54 (6.13) ml.min-1.kg-1, Maximal Power output: 4.77 (0.6) W/kg completed a 20-min time-trial self-paced exercise in three separate sessions, corresponding to three stimulation conditions: anodal, cathodal and sham. tDCS was administered before each test during 20-min at a current intensity of 2.0 mA. The anode electrode was placed over the DLPFC and the cathode in the contralateral shoulder. In each session, power output, heart rate, sRPE and EEG (at baseline and during exercise) was measured. Results: There were no differences (F = 0.31, p > 0.05) in power output between the stimulation conditions: anodal (235 W [95%CI 222-249 W]; cathodal (235 W [95%CI 222-248 W] and sham (234 W [95%CI 220-248 W]. Neither heart rate, sRPE nor EEG activity were affected by tDCS (all Ps > 0.05). Conclusion: tDCS over the left DLFC did not affect self-paced exercise performance in trained cyclists. Moreover, tDCS did not elicit any change on oscillatory brain activity either at baseline or during exercise. Our data suggest that the effects of tDCS on endurance performance should be taken with caution.